Exposure to political shows on satellite channels - Yahya, Baraa Amer; AL-Zwaini, Hussein D. (Al-Adab Journal, 2021)
The problem of research was summarized in the exposure of the public (city of Baghdad) and the exposure to political programs in satellite channels, as the problem was identified by the following main question:(What is the nature of exposure to political programs in satellite television?)By conducting a survey of the audience of the city of Baghdad, the research sample of 460 individuals was selected from the population projections for 2019 issued by the Central Bureau of Statistics of the Iraqi Ministry of Planning. The aim of the research was to detect the habits and patterns of public exposure to political programs in satellite television, as well as to determine levels of exposure to political television programs. This research is descriptive research that describes what exists by collecting, scheduling and tabulating information and data on the phenomenon and then interpreting the data and drawing conclusions, and the researcher used the survey method and the correlation method to verify the research assumptions.